2016
DOI: 10.1007/5584_2016_6
|View full text |Cite
|
Sign up to set email alerts
|

The Extracellular Matrix of Fungal Biofilms

Abstract: A key feature of biofilms is their production of an extracellular matrix. This material covers the biofilm cells, providing a protective barrier to the surrounding environment. During an infection setting, this can include such offenses as host cells and products of the immune system as well as drugs used for treatment. Studies over the past two decades have revealed the matrix from different biofilm species to be as diverse as the microbes themselves. This chapter will review the composition and roles of matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 96 publications
(142 reference statements)
0
26
0
1
Order By: Relevance
“…The ECM composition varies among different fungal species and even across different environmental conditions under which biofilm can grow ( Al-Fattani and Douglas, 2006 ; Flemming and Wingender, 2010 ; Reichhardt et al, 2015 ). As far as we are aware, the ECM composition of Pseudallescheria and Scedosporium biofilms is unknown, and further studies are therefore needed to determine its composition and whether it plays an important role in drug-sequestration, as was described in Candida biofilms ( Nett et al, 2010 ; Vediyappan et al, 2010 ; Mitchell et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ECM composition varies among different fungal species and even across different environmental conditions under which biofilm can grow ( Al-Fattani and Douglas, 2006 ; Flemming and Wingender, 2010 ; Reichhardt et al, 2015 ). As far as we are aware, the ECM composition of Pseudallescheria and Scedosporium biofilms is unknown, and further studies are therefore needed to determine its composition and whether it plays an important role in drug-sequestration, as was described in Candida biofilms ( Nett et al, 2010 ; Vediyappan et al, 2010 ; Mitchell et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the drug resistance in C. albicans is essentially multifactorial, and the production of biofilm matrix is one of the relevant resistance-related mechanisms associated with the development of biofilm, pharmacological interventions during the early phase of biofilm formation leading to the reduction of its extracellular matrix are strongly correlated with increased treatment effectiveness [ 83 ]. Numerous reports have indicated that the mechanisms responsible for the reduction in carbohydrate content of biofilm extracellular matrix are associated with changed expression of gene encoding enzymes modifying the amount of β-1,3-glucan ( FKS1, BGL2P, PHR1P, XOG1) , β-1,6-glucan ( BIG1, KRE5 ) and mannan ( PMR1 , ALG11 , MNN9 , MNN4-4 , VRG4 , VAN-1) [ 83 , 84 ].…”
Section: A New Perspective For Plants’ Components In Antifungal Thmentioning
confidence: 99%
“…The most medically relevant function of the extracellular matrix is its ability to provide a physical barrier between biofilm cells and immune system and often drugs used for treatment [ 9 , 154 , 177 ]. Fungus biofilms were reported to be up to 1000-fold more resistant to antifungal agents than planktonic cells, but the mechanism of this resistance remains unclear [ 10 , 123 ].…”
Section: Physical and Molecular Resistance In Fungal Biofilmsmentioning
confidence: 99%